1994
DOI: 10.1002/j.2334-4822.1994.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Leaders and Faculty Developers: Creating an Institutional Culture That Values Teaching

Abstract: In recent years, a great deal has been said and written about the need to improve teaching in the academy, especially in large research universities. College presidents, national associations representing higher education, private foundations, and individual faculty scholars all have challenged faculty, chairs, deans, campus administrators, and faculty developers to work together to improve support for undergraduate teaching and learning (Bok. Despite such calls for collaborative efforts to improve undergradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Trivellas and Dargenidou (2009) indicated that specific cultural archetypes are linked with different administrative services in higher education. The results of a case study from the University of Massachusetts at Amherst to “encourage a culture on campus that values working” has emphasized how important it is for the campus community—especially faculty—to feel that the administration clearly places a high value on working (Aitken & Sorcinelli, 1994, p. 64). A supportive culture may reduce the likelihood of the occurrence of employees' negative experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Trivellas and Dargenidou (2009) indicated that specific cultural archetypes are linked with different administrative services in higher education. The results of a case study from the University of Massachusetts at Amherst to “encourage a culture on campus that values working” has emphasized how important it is for the campus community—especially faculty—to feel that the administration clearly places a high value on working (Aitken & Sorcinelli, 1994, p. 64). A supportive culture may reduce the likelihood of the occurrence of employees' negative experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Significant human and financial resources are being invested in pedagogical reform efforts, but little evidence exists to indicate their widespread adoption. This circumstance suggests that scholars may be relying on anecdotes, experiences, and personal beliefs when it comes to deciding whether to respond to their campus's appeals for changes in how they teach their students (Aitken and Sorcinelli 1994).…”
mentioning
confidence: 98%
“…Relationships are core to effective CTLs, whether vertical, lateral, internal, or external (Little, ). Connections with high‐level administrators are clearly critical to garner resources, and networking and communication skills are needed to maintain close connections with central leadership (Aitkin & Sorcinelli, ; Seldin, ). Likewise, lateral relationships with academic departments and other centers enable a CTL to expand its reach.…”
Section: Relationshipsmentioning
confidence: 99%